Livistona decipiens, Ribbon Fan Palm - Mary McKenzie; Michael G. Andreu; Melissa H. Friedman; Heather V. Quintana (EDIS, 2010)
FOR 253, a 2-page fact sheet by Mary McKenzie, Michael G. Andreu, Melissa H. Friedman, and Heather V. Quintana, describes this tall and stately palm tree with draping leaves that can add a graceful touch to any yard — scientific and common names, description, allergen, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, May 2010.